2009
DOI: 10.1002/chem.200802175
|View full text |Cite
|
Sign up to set email alerts
|

Modular Synthesis of Tetrasubstituted Imidazoles and Trisubstituted Oxazoles by Aldimine Cross‐Coupling

Abstract: From five to two: The addition of deprotonated Strecker products to N‐acylimines permits the synthesis of tetrasubstituted imidazoles or trisubstituted oxazoles in three or four steps, respectively. In total, the target compounds are prepared from two aldehydes, a primary amine, an acid chloride and ammonia (see scheme).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
28
0

Year Published

2010
2010
2021
2021

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 69 publications
(29 citation statements)
references
References 24 publications
1
28
0
Order By: Relevance
“…This meant that steric effect and electronic effect had little influence on the reaction. Moreover, β-keto esters with different alkyl substituents can also react with benzylamine smoothly, furnishing the desired products in 75-82% yield (entries [4][5][6][7][8]. When the reaction substrates were switched from β-keto esters to β-diketones, the reactions can be carried out smoothly to give the corresponding products with good yields (entries 9 and 10).…”
Section: Resultsmentioning
confidence: 99%
“…This meant that steric effect and electronic effect had little influence on the reaction. Moreover, β-keto esters with different alkyl substituents can also react with benzylamine smoothly, furnishing the desired products in 75-82% yield (entries [4][5][6][7][8]. When the reaction substrates were switched from β-keto esters to β-diketones, the reactions can be carried out smoothly to give the corresponding products with good yields (entries 9 and 10).…”
Section: Resultsmentioning
confidence: 99%
“…We first focused on the N-arylation of imidazole, since 1-arylimidazoles are important motifs found in a series of medicinally important compounds that have been exploited as key building blocks for the synthesis of N-heterocyclic carbenes [30][31][32] . As shown in Table 1, among the different bases tested in the catalysis under the same reaction conditions, NaOH gave the best isolated yield of around 96% after reaction for 4 h( Table 1, Entry 1).…”
Section: Resultsmentioning
confidence: 99%
“…[8][9][10][11][12][13][14][15][16][17][18] The pioneering chemical synthesis of α-amino acids reported by Adolph Strecker in 1850 made use of their close relationship with α-aminonitriles and even today, the Strecker synthesis is still used for the industrial scale synthesis of α-amino acids like methionine. 19 Due to the strong anion stabilizing capacity of the nitrile group and the latent iminium ion reactivity, [20][21][22][23] α-aminonitriles are not only useful precursors to amino acids but also versatile building blocks for the synthesis of a wide variety of nitrogen-containing compounds 24, 25 including diverse N-heteroarenes, [26][27][28] aliphatic amine derivatives 29,30 or alkaloids [31][32][33][34][35][36][37][38][39] . We found that N-mono-and N-unsubstituted α-aminonitriles derived from aromatic or heteroaromatic aldehydes can be deprotonated quantitatively in α-position to furnish stabilized α-aminocarbanion equivalents and in contrast to their counterparts derived from aliphatic aldehydes, no N-protection is required.…”
Section: Page 1 Of 24 Acs Paragon Plus Environmentmentioning
confidence: 99%